Adhesion characteristics of porcine pancreatic islets and exocrine tissue to coating materials. Issue 3 (4th May 2018) - Nakashima, Yoshiki; Miyagi-Shiohira, Chika; Kobayashi, Naoya; Saitoh, Issei; Watanabe, Masami; Noguchi, Hirofumi
ABSTRACT: Since the report of the Edmonton protocol in 2000, islet transplantation has been implemented worldwide, and xenotransplantation using porcine islets has also been reported. In addition, many basic experiments using pancreatic islets and exocrine tissue after isolation have been reported. Recently, exocrine cells have been found to be essential for inducing the differentiation of pancreatic islets. Therefore, the importance of the culture conditions for pancreatic tissue when conducting experiments using pancreatic tissue is also increasing. In this study, we focused on the coat material and examined the adhesive properties of porcine pancreatic islets and exocrine tissue after isolation. Porcine islet isolation was performed, and isolated islets (purity ≥95%) and exocrine tissue (purity ≥99%) were used to achieve adhesion to several extracellular matrixes, fibronectin, collagen type I, collagen type IV, laminin I, fibrinogen, and bovine serum albumin (BSA). DMEM with 0.5% FBS was used as the assay medium. For exocrine tissue, the adhesion was promoted in fibronectin, collagen type I, laminin I, and fibrinogen. The adhesive ability to fibronectin was more than twice that to BSA, while the adhesive ability to collagen type I, laminin I, and fibrinogen was less than twice that to BSA. For islets, the adhesive ability to fibronectin was weaker than that of exocrine tissue. Furthermore, the adhesion effect in fibronectin was obtained within 30 minutes and in medium containing little serum for both islets and exocrine tissues. These data suggest that fibronectin may be useful for the adhesion of pancreatic tissue.